Program Niha’i Santri: Pola Pengembangan Pedagogik Guru - Yuniatul Jannah (Fakta: Jurnal Pendidikan Agama Islam, 2021)
This Article conclusion the findings of this study proves that the niha'i program has great relevance in fostering the pedagogical competence of service teachers conducted at the Nurul Huda Islamic Boarding School in Pakandangan Barat Bluto Sumenep. The niha'i program is geared towards how children learn to become professional educators. The focus of the research is how is the implementation and how is the relevance of the niha'i program in fostering the pedagogical competence of midwifery teachers at Pondok Pesantren Nurul Huda Pakandangan Barat Bluto Sumenep Madura in 2019?This research uses a qualitative approach. Data collection techniques used were interviews, observation and documentation. The data analysis used consisted of three interacting analyzes, namely data reduction, data presentation and conclusion drawing. From the discussion of the research it can be concluded that the implementation of the Niha'i program in fostering the pedagogical competence of service teachers at Nurul Huda Islamic Boarding School begins with the planning stage which socializes to final grade students, implementation is adjusted to a previously planned schedule and evaluation in the form of a document of work results. students who are assessed and validated by the supervisors. While the relevance of the niha'i program is 1) Afternoon teaching, namely the teacher obtains a complete picture of students 'initial abilities and a broad picture of the experiences that students have, 2) 'Amaliyatu-t-tadris on the characteristics of teachers, including teachers must be prepared with the material to be taught, have a cheerful face and communicate well and fluently, and are in good health, 3) Mutola'atul polar is the ability of students to copy and write books or Kutubu-t-Turats from a computer using the Maktabah Syamilah program. 4) Bahtul ilmy is the teacher's writing ability with khat naskh and for footnote with khat riq'ah.